Evaluation of Antidiabetic Drug use Profile in Outpatients at A Private Hospital in Bandar Lampung City - Frenca Elsa Sitanala; Louis Madalena; Marvel Reuben Suwitono (Jurnal Biologi Tropis, 2026)
Diabetes mellitus is a long-lasting metabolic condition marked by high blood sugar levels resulting from insufficient insulin production. This study aims to evaluate the profile of antidiabetic drug use in outpatients with diabetes mellitus at a private hospital in Bandar Lampung and assess its compliance with current treatment guidelines. This study employed a non-experimental method with a retrospective descriptive design based on medical records and outpatient prescriptions from January to July 2025. The data analyzed included gender, age, comorbidities, and the types of antidiabetic drugs used. The results showed that type 2 diabetes mellitus patients were more prevalent in women (60.78%) than in men (39.22%), with the largest group of diabetes mellitus patients falling within the 45–60 age group. Most patients also had comorbidities, with hypertension being the most common. The pattern of medication use showed that biguanides, particularly metformin, were the most commonly prescribed drugs as first-line therapy. In general, the use of antidiabetic drugs in outpatients at the hospital was in accordance with the PERKENI treatment guidelines.